Unexpected difficult airway management in a transgender female patient - Vowles, B. J. (John Wiley and Sons Inc., 2020)

(untitled) (Anaesth Rep)
A transgender female patient, who had previously undergone gender‐confirming feminisation surgery to the face and larynx, was scheduled for thoracic surgery requiring one‐lung ventilation. We encountered unexpected difficult airway management and difficulty inserting an appropriately‐sized double‐lumen tube. A size 41Fr double‐lumen tube, which is selected commonly for biological males, was used eventually for lung isolation and subsequently exchanged for a size 6.5 single‐lumen tracheal tube at the end of the case, before successful extubation with a staged extubation set. It is important to highlight the challenges faced, as the care of transgender patients is likely to be unfamiliar to most anaesthetists, despite the increase in the number of gender‐confirming procedures performed. Many of these procedures involve the face and airway and can result in significant challenges for airway management, including appropriate sizing of tracheal tubes and their correct placement. It is also possible that patients may not volunteer a history of these procedures and it should be enquired about specifically as part of the anaesthetic pre‐assessment.